Authentication of fattening diet of Iberian pigs according to their volatile compounds profile from raw subcutaneous fat. - Narváez-Rivas, M; Pablos, F; Jurado, J M; León-Camacho, M (Analytical and bioanalytical chemistry, 2011)
The composition of volatile components of subcutaneous fat from Iberian pig has been studied. Purge and trap gas chromatography-mass spectrometry has been used. The composition of the volatile fraction of subcutaneous fat has been used for authentication purposes of different types of Iberian pig fat. Three types of this product have been considered, montanera, extensive cebo and intensive cebo. With classification purposes, several pattern recognition techniques have been applied. In order to find out possible tendencies in the sample distribution as well as the discriminant power of the variables, principal component analysis was applied as visualisation technique. Linear discriminant analysis (LDA) and soft independent modelling by class analogy (SIMCA) were used to obtain suitable classification models. LDA and SIMCA allowed the differentiation of three fattening diets by using the contents in 2,2,4,6,6-pentamethyl-heptane, m-xylene, 2,4-dimethyl-heptane, 6-methyl-tridecane, 1-methoxy-2-propanol, isopropyl alcohol, o-xylene, 3-ethyl-2,2-dimethyl-oxirane, 2,6-dimethyl-undecane, 3-methyl-3-pentanol and limonene.
Keywords: Gas chromatography−mass spectrometry; iberian pig; pattern recognition; subcutaneous fat; volatile compounds

Rapid characterization of dry cured ham produced following different PDOs by proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). - Del Pulgar, José Sánchez; Soukoulis, Christos; Biasioli, Franco; Cappellin, Luca; García, Carmen; Gasperi, Flavia; Granitto, Pablo; Märk, Tilmann D.; Piasentier, Edi; Schuhfried, Erna (Talanta, 2011)
In the present study, the recently developed proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS) technique was used for the rapid characterization of dry cured hams produced according to 4 of the most important Protected Designations of Origin (PDOs): an Iberian one (Dehesa de Extremadura) and three Italian ones (Prosciutto di San Daniele, Prosciutto di Parma and Prosciutto Toscano). In total, the headspace composition and respective concentration for nine Spanish and 37 Italian dry cured ham samples were analyzed by direct injection without any pre-treatment or pre-concentration. Firstly, we show that the rapid PTR-ToF-MS fingerprinting in conjunction with chemometrics (Principal Components Analysis) indicates a good separation of the dry cured ham samples according to their production process and that it is possible to set up, using data mining methods, classification models with a high success rate in cross validation. Secondly, we exploited the higher mass resolution of the new PTR-ToF-MS, as compared with standard quadrupole based versions, for the identification of the exact sum formula of the mass spectrometric peaks providing analytical information on the observed differences. The work indicates that PTR-ToF-MS can be used as a rapid method for the identification of differences among dry cured hams produced following the indications of different PDOs and that it provides information on some of the major volatile compounds and their link with the implemented manufacturing practices such as rearing system, salting and curing process, manufacturing practices that seem to strongly affect the final volatile organic profile and thus the perceived quality of dry cured ham.
The following values have no corresponding Zotero field: accession-num: 21645714
Keywords: Animals; Data Mining; Dry cured ham; Flavour compounds; Food Handling; Food Handling: methods; Italy; Mass spectrometry; Mass Spectrometry: methods; Meat Products; Meat Products: analysis; PDO; PTR-MS; PTR-ToF-MS; Spain; Swine; volatile compounds; Volatile Organic Compounds

Volatile Compounds in Samples of Cork and also Produced by Selected Fungi - Barreto, M. C.; Boas, L. Vilas; Carneiro, L. C.; Rom, M. V. San; Vilas Boas, L.; San Romão, M. V. (Journal of Agricultural and Food Chemistry, 2011)
The production of volatile compounds by microbial communities of cork samples taken during the cork manufacturing process was investigated. The majority of volatiles were found in samples collected at two stages: resting after the ﬁrst boiling and nontreated cork disks. Volatile proﬁles produced by microbiota in both stages are similar. The releasable volatile compounds and 2,4,6-trichloroanisole (TCA) produced in cork-based culture medium by ﬁve isolated fungal species in pure and mixed cultures were also analyzed by gas chromatography coupled with mass spectrometry (GC-MS).The results showed that 1-octen-3-ol and esters of fatty acids (medium chain length C8C20) were the main volatile compounds produced by either pure fungal species or their mixture. Apparently,Penicillium glabrum is the main contributor to the overall volatile composition observed in the mixed culture. The production of releasable TCA on cork cannot be attributed to any of the assayed fungal isolates.
The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: 2; 2.4.6-trichloroanisole; 4; 6-trichloroanisole; Cork; fungi; volatile compounds

Volatile and carbohydrate composition of rare unifloral honeys from Spain - Delafuente, E.; Sanz, M.; Martinezcastro, I.; Sanz, J.; Ruizmatute, A. (Food Chemistry, 2007)
Volatile composition and carbohydrate content of Spanish honey samples from uncommon botanical origins have been studied by gas chromatography coupled to mass spectrometry. About 100 volatile compounds were identiﬁed; some of them appeared to be characteristic of particular honey types, such as methyl salycilate in willow (Salix spp.), 2,6,6-trimethyl-2,4-cycloheptadien-1-one (eucarvone) in almond tree (Prunus dulcis) and isophorone in strawberry-tree (Arbutus unedo). Concentration ranges for major carbohydrates were similar to those previously reported in other honeys with diﬀerent botanical origins, although concentrations of maltulose in avocado honeys (Persea americana) and of melezitose in Quercus ilex honeys were higher. Some carbohydrate alcohols could also be considered as markers of honey botanical origin, such as quercitol for Q. ilex and perseitol for avocado.
Keywords: carbohydrates; gc; GC-MS; honey; ms; polyalcohols; volatile compounds

Volatile composition and contribution to the aroma of Spanish honeydew honeys. Identification of a new chemical marker - Castro-Vazquez, L; Diaz-Maroto, M C; Perez-Coello, M S (JOURNAL OF AGRICULTURAL AND FOOD CHEMISTRY, 2006)
Honeydew honeys from holm-oak, oak, and forest were isolated for aroma compounds by simultaneous distillation-extraction and analyzed by gas chromatography-mass spectrometry. In all, 66 volatile components were identified and quantified. trans-Oak lactone, a characteristic volatile component of oak wood, is proposed as a new chemical marker for the plant origin of honeydew honeys. Other compounds, such as aminoacetophenone and propylanisol, could be considered characteristic of holm-oak honeydew honeys. A total of 15 volatile compounds presented odor activity values (OAVs) greater than 1, with phenylacetaldehyde and beta-damascenone being those with the highest OAVs.
Keywords: aroma; gas chromatography; honey; honeydew honey; volatile compounds